FORMULATION AND IN VITRO EVALUATION OF LOSARTAN POTASSIUM MUCOADHESIVE BUCCAL TABLETS - Velmurugan, Sellappan; Srinivas, P (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The Losartan potassium mucoadhesive buccal tablet were prepared using mucoadhesive polymers such as Carbopol 940P, pectin, sodium CMC, Sodium alginate, HPMC K4M, HPMC K15M and HPMC K100M in alone and in combination as release retarding agent to prolong the drug release and to avoid first pass metabolism. Methods: The mucoadhesive buccal tablets were prepared by direct compression method. The prepared mucoadhesive buccal tablets wereÂ evaluatedÂ forÂ physicochemicalÂ parametersÂ suchÂ asÂ hardness, thickness uniformity, weight variation, and surface pH and moisture absorption studies. The prepared buccal tablets were also evaluated for mucoadhesive strength, exâ€vivo residence time, in vitro drugÂ releaseÂ andÂ drugÂ permeationÂ throughÂ porcineÂ buccalÂ mucosa.Â TheÂ drugÂ excipients compatability was evaluated by DSC studies. Â Results: ExÂ vivo mucoadhesiveÂ strength,Â exâ€ vivo residence time and in vitro release studies showed that formulation F10 containing 1:1.25 ratio of drug and polymer combination showed satisfactory bioadhesive and exhibited optimum drug release (91.33 %Â after 12hrs). DSC results showed no evidence of interaction between the Losartan potassium and mucoadhesive polymers. The results indicated that suitable bioadhesive buccal tablets with desired permeability could be prepared. The Stability of Losartan potassium mucoadhesive buccal tablets was determined in natural human saliva; it was found that both Losartan potassium and buccal tablets were stable in human saliva. Â Conclusion: Hence different mucoadhesive polymers (Carbopol 940P, pectin, Sodium CMC, Sodium alginate and HPMC different grades) in various proportions can be used to prepare mucoadhesive buccal tablets of Losartan potassium having prolonged therapeutic effect with enhanced patience compliance by avoiding first pass metabolism. Â Keywords: LosartanÂ potassium,Â mucoadhesiveÂ buccalÂ tablets,Â HPMCÂ K100,CarbopolÂ 940P,Â Â Â Â Â Â Â Formulation, Evaluation